2016
DOI: 10.1177/1087057115618347
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Microscale Thermophoresis Screening Approach for Fragment-Based Lead Discovery

Abstract: Fragment-based lead discovery has proved to be an effective alternative to high-throughput screenings in identifying chemical matter that can be developed into robust lead compounds. The search for optimal combinations of biophysical techniques that can correctly and efficiently identify and quantify binding can be challenging due to the physicochemical properties of fragments. In order to minimize the time and costs of screening, optimal combinations of biophysical techniques with maximal information content,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 15 publications
1
78
0
1
Order By: Relevance
“…The thermal unfolding of 5 g/L PPI13 in different formulations was studied with nanoDSF ® . 21,22 The samples were filled in standard glass capillaries, the capillaries were sealed and placed in a Prometheus ® NT.48 (NanoTemper Technologies, Munich, Germany). The device was used to linearly change the sample temperature from 25 C to 100 C with a ramp of 0.1 C/min.…”
Section: High-throughput Fluorimetric Analysis Of Thermal Protein Unfmentioning
confidence: 99%
“…The thermal unfolding of 5 g/L PPI13 in different formulations was studied with nanoDSF ® . 21,22 The samples were filled in standard glass capillaries, the capillaries were sealed and placed in a Prometheus ® NT.48 (NanoTemper Technologies, Munich, Germany). The device was used to linearly change the sample temperature from 25 C to 100 C with a ramp of 0.1 C/min.…”
Section: High-throughput Fluorimetric Analysis Of Thermal Protein Unfmentioning
confidence: 99%
“…In order to ensure that the variation in uorescence was associated with binding, we performed a standard denaturation test (SD test) as described previously. 23 For the SD test of full-length AQP2 with LIP5, four samples were prepared in the same manner as for the MST experiment above, corresponding to high, medium and low concentration of LIP5 (2450 nM, 322 nM and 28 nM) as well as labelled full-length AQP2 alone. For the AQP0 peptide, three samples were prepared corresponding to high and low concentrations of AQP0 peptide (5.375 nM and 0.67 nM) and labelled CaM alone.…”
Section: Denaturation Testmentioning
confidence: 99%
“…2628 The use of MST is increasingly being reported in fragment-based drug discovery, 23,24,3033 including kinases such as p38α 30 and MEK1, 31 and the bromodomain BRD9. 32 In both the MEK1 study by Sanofi in collaboration with NanoTemper and the BRD9 study by Boehringer Ingelheim, MST was used to confirm the binding of fragments identified by SPR and DSF, as well as to identify additional hits not detected by the other techniques.…”
Section: Microscale Thermophoresismentioning
confidence: 99%
“…25 This explains why MST is gaining popularity as a technique for fragment screening, because it allows the study of weak-affinity fragments titrated up to 10 mM. 31,32 In addition, MST is described as offering a wide detection range, from low-millimolar to picomolar affinities, when using NanoTemper’s dedicated Monolith NT.115 Pico instrument. 28 In general, dissociation constants (K d ) within twofold of the protein concentration can be accurately quantified.…”
Section: Microscale Thermophoresismentioning
confidence: 99%
See 1 more Smart Citation